Mining the Moraxella catarrhalis Genome: Identification of Potential Vaccine Antigens Expressed during Human Infection - Ruckdeschel, Elizabeth A. (American Society for Microbiology (ASM), 2008)
Moraxella catarrhalis is an important cause of respiratory infections in adults and otitis media in children. Developing an effective vaccine would reduce the morbidity, mortality, and costs associated with such infections. An unfinished genome sequence of a strain of M. catarrhalis available in the GenBank database was analyzed, and open reading frames predicted to encode potential vaccine candidates were identified. Three genes encoding proteins having molecular masses of approximately 22, 75, and 78 kDa (designated Msp [Moraxella surface proteins]) (msp22, msp75, and msp78, respectively) were determined to be conserved by competitive hybridization using a microarray, PCR, and sequencing of the genes in clinical isolates of M. catarrhalis. The genes were transcribed when M. catarrhalis was grown in vitro. These genes were amplified by PCR and cloned into Escherichia coli expression vectors. Recombinant proteins were generated and then studied using enzyme-linked immunosorbent assays with preacquisition and postclearance serum and sputum samples from 31 adults with chronic obstructive pulmonary disease (COPD) who acquired and cleared M. catarrhalis. New antibody responses to the three proteins were observed for a small proportion of the patients with COPD, indicating that these proteins were expressed during human infection. These studies indicate that the Msp22, Msp75, and Msp78 proteins, whose genes were discovered using genome mining, are highly conserved among strains, are expressed during human infection with M. catarrhalis, and represent potential vaccine antigens.